EKSPLORASI ARSITEKTUR MADURA: DARI RUMAH ADAT TANEAN LANJHANG KE LITERASI SPASIAL DALAM PEMBELAJARAN MATEMATIKA - Supriliyanti, Novi; Fijriyah, Izzah; Wardhani, Indah Setyo; Fadilah, Nur; Hariani, Shintia Shepti (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The architecture of the tanean lanjhang traditional house is a bridge between culture and spatial literacy, because tanean lanjhang architecture contains elements of visualization, reasoning, and communication that can be integrated in mathematics learning. The purpose of this study is to explore spatial literacy ideas from tanean lanjhang architecture in mathematics learning. This type of research is qualitative research with the researcher as a participant. The research instrument was an observation sheet containing spatial literacy indicators and mathematical elements. Data collection techniques are: observation, interview, documentation, and literature study. The research subject was the taneyan lanjhang house in Cempaka Hamlet, Candi Burung Village, Proppo-Pamekasan. The results concluded that in the architecture of the tanean lanjhang traditional house, there are spatial literacy ideas in the form of visualization, reasoning, and communication that can be used to explain the concepts of geometry, measurement, number addition, fractions, and (row, series, arithmetic). Implementation of research results in the form of preparation of culture-based materials, Learner Worksheets (LKPD), or culture-based assessments.